(The Assesment of Cooking Oil Formulas Using Mathematical Approach) - Shinta D; Sirait -; Sutrida Nurti; Ingriani - (Warta Industri Hasil Pertanian, 1990)
The formulation technique of vegetable cooking oil had been carried out using basic mathematical method. The study was aimed at preparing formulas in order to fulfil the need for healthy cooking oil. The oil used was coconut oi, palm oi, peanut oil, corn oil, and sesame oil. Four formulas had been obtained. The analysis showed that the formulated oil meet the specification of healthy oil qualitatively and quantitatively.